Impact of a school-based intervention to promote fruit intake: a cluster randomized controlled trial. (July 2016) - Rosário, R.; Araújo, A.; Padrão, P.; Lopes, O.; Moreira, A.; Abreu, S.; Vale, S.; Pereira, B.; Moreira, P.
Abstract: Objective: There is evidence that fruit consumption among school children is below the recommended levels. This study aims to examine the effects of a dietary education intervention program me, held by teachers previously trained in nutrition, on the consumption of fruit as a dessert at lunch and dinner, among children 6–12 years old. Study design: This is a randomized trial with the schools as the unit of randomisation. Methods: A total of 464 children (239 female, 6–12years) from seven elementary schools participated in this cluster randomized controlled trial. Three schools were allocated to the intervention and four to the control group. For the intervention schools, we delivered professional development training to school teachers (12 sessions of 3 h each). The training provided information about nutrition, healthy eating, the importance of drinking water and healthy cooking activities. After each session, teachers were encouraged to develop classroom activities focused on the learned topics. Sociodemographic was assessed at baseline and anthropometric, dietary intake and physical activity assessments were performed at baseline and at the end of the intervention. Dietary intake was evaluated by a 24-h dietary recall and fruit consumption as a dessert was gathered at lunch and dinner. Results: Intervened children reported a significant higher intake in the consumption of fruit compared to the controlled children at lunch ( P = 0.001) and at dinner ( P = 0.012), after adjusting for confounders. Conclusions: Our study provides further support for the success of intervention programmes aimed at improving the consumption of fruit as a dessert in children. Highlights: Childhood is an important period to improve healthy eating behaviours. Interventions that aim to improve healthy eating habits in schools have been implemented, but with variable impact. This study provides further support for the success of interventions that aim to enhance children's fruit intake. Implementing similar interventions can be promising to support increase fruit consumption at dessert.